Evaluation of rational use of drugs used in hypertension in a tertiary care hospital: a cross-sectional observational study - Suneel I. Majagi; Devasena Manohar; Jagadeesh Gaddeppanavar (International Journal of Basic & Clinical Pharmacology, 2026)
Background: Hypertension is a major public health problem due to increased morbidity, mortality and cost to the public. Various group of antihypertensive drugs are used in the management of hypertension. Criteria like medications appropriate to the clinical needs, required individual doses, adequate period and lowest cost are considered during rational use of medicines. Irrational prescribing can cause increased morbidity, mortality, adverse drug reactions (ADRs), and economic burden. World Health Organization (WHO) stress the need to promote rational use of drugs. Hence the present study has been planned to evaluate rational use of antihypertensive drugs according to the WHO guidelines. Methods: Present study design is a cross-sectional observational study. Data regarding antihypertensive drugs was collected as per WHO guidelines viz., details of prescriptions, patient counselling and drugs. Details of co-morbid illnesses, ADRs, precautions and contraindications were also noted. Standard statistical tests were used to analyse the data and the study was approved by the institutional ethics committee. Results: Various criteria required for rational use of medicines in regard to prescription, patient counsel and drugs were followed in all (100%) the patients. Diuretics caused ADRs in a greater number of patients. More patients suffered from ADRs affecting central nervous system followed by gastro intestinal tract, and cardio vascular system. No precautions and contraindications were found for any of the prescribed drug. Conclusions: WHO-rational use criteria and joint national committee (JNC) 8 guidelines were adhered. Medical council registration number and stamp have to be mentioned in the prescription. Prescriptions of generic name drugs must be promoted.